Usefulness of current candidate genetic markers to identify childhood cancer patients at risk for platinum-induced ototoxicity: Results of the European PanCareLIFE cohort study - Langer, Thorsten; Clemens, Eva; Broer, Linda; Maier, Lara; Uitterlinden, André G; de Vries, Andrica C H; van Grotel, Martine; Pluijm, Saskia F M; Binder, Harald; Mayer, Benjamin; von dem Knesebeck, Annika; Byrne, Julianne; et al. (European journal of cancer (Oxford, England, 2020)
BACKGROUND: Irreversible sensorineural hearing loss is a common side effect of platinum treatment with the potential to significantly impair the neurocognitive, social and educational development of childhood cancer survivors. Genetic association studies suggest a genetic predisposition for cisplatin-induced ototoxicity. Among other candidate genes, thiopurine methyltransferase (TPMT) is considered a critical gene for susceptibility to cisplatin-induced hearing loss in a pharmacogenetic guideline. The aim of this cross-sectional cohort study was to confirm the genetic associations in a large pan-European population and to evaluate the diagnostic accuracy of the genetic markers. METHODS: Eligibility criteria required patients to be aged less than 19 years at the start of chemotherapy, which had to include cisplatin and/or carboplatin. Patients were assigned to three phenotype categories: no, minor and clinically relevant hearing loss. Fourteen variants in eleven candidate genes (ABCC3, OTOS, TPMT, SLC22A2, NFE2L2, SLC16A5, LRP2, GSTP1, SOD2, WFS1 and ACYP2) were investigated. Multinomial logistic regression was performed to model the relationship between genetic predictors and platinum ototoxicity, adjusting for clinical risk factors. Additionally, measures of the diagnostic accuracy of the genetic markers were determined. RESULTS: 900 patients were included in this study. In the multinomial logistic regression, significant unique contributions were found from SLC22A2 rs316019, the age at the start of platinum treatment, cranial radiation and the interaction term [platinum compound]∗[cumulative dose of cisplatin]. The predictive performance of the genetic markers was poor compared with the clinical risk factors. CONCLUSIONS: PanCareLIFE is the largest study of cisplatin-induced ototoxicity to date and confirmed a role for the polyspecific organic cation transporter SLC22A2. However, the predictive value of the current genetic candidate markers for clinical use is negligible, which puts the value of clinical factors for risk assessment of cisplatin-induced ototoxicity back into the foreground.
Keywords: Genetic Predisposition to Disease; Cross-Sectional Studies; Pharmacogenomic Variants; Carboplatin; Anti-neoplastic drugs; jednonukleotidový polymorfismus; Childhood cancer; transportér organických kationtů 2; Genetic markers; Pharmacogenomic Testing; Retrospective Studies; Hearing; kojenec; Europe; mladiství; Cisplatin; věk při počátku nemoci; Evropa; Risk Assessment; cisplatina; mužské pohlaví; Infant; průřezové studie; Prospective Studies; sluch; Antineoplastic Agents; ototoxicita; dítě; karboplatina; farmakogenomické testování; Child; Hearing Loss, Sensorineural; Neoplasms; Infant, Newborn; Child, Preschool; Ototoxicity; Adverse drug reaction; ženské pohlaví; přežívající onkologičtí pacienti; protinádorové látky; genetické asociační studie; novorozenec; předškolní dítě; percepční nedoslýchavost; prospektivní studie; retrospektivní studie; hodnocení rizik; Humans; nádory; Drug-induced ototoxicity; Cancer Survivors; farmakogenomické varianty; Pharmacogenetics; Age of Onset; Cancer survivors; Organic Cation Transporter 2; rizikové faktory; Cisplatin: carboplatin; Genetic Association Studies; genetická predispozice k nemoci; Female; Risk Factors; Adolescent; Multicenter cohort study; lidé; Male; Polymorphism, Single Nucleotide